2021
DOI: 10.1002/art.41569
|View full text |Cite
|
Sign up to set email alerts
|

Can Dual‐Energy Computed Tomography Be Used to Identify Early Calcium Crystal Deposition in the Knees of Patients With Calcium Pyrophosphate Deposition?

Abstract: Objective. To assess the ability of dual-energy computed tomography (DECT) in identifying early calcium crystal deposition in menisci and articular cartilage of the knee, depending on the presence/absence of chondrocalcinosis seen on conventional CT. Methods. One hundred thirty-two knee DECT scans from patients with suspected crystal-associated arthropathy were reviewed and assigned to a calcium pyrophosphate deposition (CPPD) group (n = 50) or a control group (n = 82). Five DECT attenuation parameters were me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 19 publications
(38 reference statements)
1
13
0
Order By: Relevance
“…Current reconstruction protocols only allow colour coding of one variable, perhaps future protocols will allow coding for two variables with independent settings. All CPP crystal arthritis patients who demonstrated CPP typical depositions on radiographs also displayed CPP positive findings on DECT, in line with a previous study by Budzik et al, which also showed that DECT was not able to reliably identify CPP deposits in patients unless chondrocalcinosis was already visible on conventional X-rays [34]. Ultrasound sensitivity and specificity were 92% and 83% respectively for gout.…”
Section: Discussionsupporting
confidence: 86%
“…Current reconstruction protocols only allow colour coding of one variable, perhaps future protocols will allow coding for two variables with independent settings. All CPP crystal arthritis patients who demonstrated CPP typical depositions on radiographs also displayed CPP positive findings on DECT, in line with a previous study by Budzik et al, which also showed that DECT was not able to reliably identify CPP deposits in patients unless chondrocalcinosis was already visible on conventional X-rays [34]. Ultrasound sensitivity and specificity were 92% and 83% respectively for gout.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, one can ask whether we have used the best imaging method to detect crystals, since promising studies about the use of ultrasound37 in the identification of CPPD have been published while the significance of DECT seems less clear 38 39. In this study we have not systematically used ultrasound to detect crystals in hand or feet due to lack of standardisation.…”
Section: Discussionmentioning
confidence: 99%
“…ability and criterion validity with good results (13,18,19); while DECT has proven helpful in the diagnosis of gout, and emerging data suggest that it may be promising in calcium crystal recognition and differentiation as well (20,21). Nonetheless, SFA via compensated polarized light microscopy is still considered the gold standard for the identification and diagnosis of CPPD-related arthropathies (1).…”
Section: Original Papermentioning
confidence: 99%